2009
DOI: 10.1128/mcb.00116-09
|View full text |Cite
|
Sign up to set email alerts
|

MST Kinases Monitor Actin Cytoskeletal Integrity and Signal via c-Jun N-Terminal Kinase Stress-Activated Kinase To Regulate p21Waf1/Cip1 Stability

Abstract: As well as providing a structural framework, the actin cytoskeleton plays integral roles in cell death, survival, and proliferation. The disruption of the actin cytoskeleton results in the activation of the c-Jun N-terminal kinase (JNK) stress-activated protein kinase (SAPK) pathway; however, the sensor of actin integrity that couples to the JNK pathway has not been characterized in mammalian cells. We now report that the mammalian Ste20-like (MST) kinases mediate the activation of the JNK pathway in response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 60 publications
1
55
0
2
Order By: Relevance
“…S4 in the supplementary material), other members of the pathway might be mislocalized in the presence of excess Factin. Interestingly, in mouse fibroblasts, the Hpo orthologs MST1 and MST2 colocalize with F-actin structures and are activated upon F-actin depolymerization (Densham et al, 2009), suggesting that by tethering Hpo pathway components, F-actin dynamics modulates their activity. Finally, the F-actin network might act as a mechanical transducer.…”
Section: Mechanisms By Which F-actin Regulates Hippo Signaling Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…S4 in the supplementary material), other members of the pathway might be mislocalized in the presence of excess Factin. Interestingly, in mouse fibroblasts, the Hpo orthologs MST1 and MST2 colocalize with F-actin structures and are activated upon F-actin depolymerization (Densham et al, 2009), suggesting that by tethering Hpo pathway components, F-actin dynamics modulates their activity. Finally, the F-actin network might act as a mechanical transducer.…”
Section: Mechanisms By Which F-actin Regulates Hippo Signaling Activitymentioning
confidence: 99%
“…Interestingly, the Merlin-actin cytoskeleton association is required for growth suppression and inhibition of epidermal growth factor (EGFR) signaling (Curto and McClatchey, 2008). Moreover, F-actin depolymerization promotes activation of the Hpo orthologs MST1 and MST2 in mouse fibroblasts (Densham et al, 2009). These observations suggest a role for Factin dynamics in modulating Hpo pathway activity.…”
Section: Introductionmentioning
confidence: 99%
“…In mammalian cells, Mst1/2 are also activated by binding to Ras association domain family (RASSF) proteins (Oh et al, 2006;Guo et al, 2007) possibly due to alteration of Mst1/2 subcellular localization (Khokhlatchev et al, 2002;Praskova et al, 2004). Recently, Mst1/2 were reported to partially co-localize with actin cytoskeleton, disruption of which leads to mild activation of the kinase (Densham et al, 2009). The activation of Mst1/2 leads to phosphorylation and activation of their direct substrates, Lats1/2 (Chan et al, 2005).…”
Section: The Mammalian Hippo Pathwaymentioning
confidence: 99%
“…Several studies indicated that the Hippo pathway regulates actin cytoskeleton in Drosophila (Fang and Adler, 2010;Fernández et al, 2011;Lucas et al, 2013). Others demonstrated the interaction of some of the core Hippo pathway components with F-actin regulators and with β-actin itself (Hirota et al, 2000;Yang et al, 2004;Densham et al, 2009;Rauskolb et al, 2011;Visser-Grieve et al, 2011). Although the biological signifi cance of this reverse regulation is not fully understood, it may play an important role in establishing a feedback loop.…”
Section: Introductionmentioning
confidence: 99%
“…In NIH3T3 cells, immunohistochemistry identifi ed the co-localization between actin cytoskeleton and Mst2. Moreover, inactivation of Rho GTPase by C3 or disruption of F-actin by LatB or CytoD induced the kinase activity of Mst2 (Densham et al, 2009). Understanding if this regulation of Mst2 by actin cytoskeleton activates Hippo pathway needs more examinations.…”
mentioning
confidence: 99%